Evolutionary History of the Marchantia polymorpha Complex - Linde, Anna-Malin; Sawangproh, Weerachon; Cronberg, Nils; Szövényi, Péter; Lagercrantz, Ulf (Frontiers in Plant Science, 2020)
The potential role of introgression in evolution has gained increased interest in recent years. Although some fascinating examples have been reported, more information is needed to generalize the importance of hybridization and introgression for adaptive divergence. As limited data exist on haploid dominant species, we analyzed genomes of three subspecies of the liverwort Marchantia polymorpha. We used available genomic data for subsp. ruderalis and carried out whole-genome (PacBio) sequencing for one individual each of subsp. montivagans and subsp. polymorpha as well as Illumina resequencing of additional genomes for all three subspecies. The three subspecies were compared against M. paleacea as outgroup. Our analyses revealed separation of the three taxa, but all three possible topologies were richly represented across the genomes, and the underlying divergence order less obvious. This uncertainty could be the result of the divergence of the three subspecies close in time, or that introgression has been frequent since divergence. In particular, we found that pseudo-chromosome 2 in subsp. montivagans was much more diverged than other parts of the genomes. This could either be explained by specific capture of chromosome 2 from an unknown related species through hybridization or by conservation of chromosome 2 despite intermittent or ongoing introgression affecting more permeable parts of the genomes. A higher degree of chromosomal rearrangements on pseudo-chromosome 2 support the second hypothesis. Species tree analyses recovered an overall topology where subsp. montivagans diverged first and subsp. ruderalis and subsp. polymorpha appeared as sister lineages. Each subspecies was associated with its own chloroplast and mitochondrial haplotype group. Our data suggest introgression but refute a previous hypothesis that subsp. ruderalis is a new stabilized hybrid between the other two subspecies.